A Tool Model Group (TMG) development to enhance student performance - Tawafak, Ragad Moufaq; Alsewari, Abdul Rahman Ahmed; Malik, Sohail Iqbal; Al-Farsi, Ghaliya Musalam Salim (Institute of Electrical and Electronics Engineers Inc., 2021)
Educational institutions in different contexts of the world are increasingly working on exploring the potential of educational development and challenges that might enhance student performance. Still, there are missing benefits of using applications that directly impact the enhancement of student performance in Oman. This paper aims to create a "Tool Model Group"(TMG) model to improve student performance using technological learning techniques in modified evaluation to enhance academic performance. In the first phase of this study, a systematic review of the existing literature was conducted to determine the degree of acceptability and effectiveness of existing applications in e-learning. The second stage involved designing a model for the hybrid e-learning tools. It is followed by a system efficiency check that can measure the technology's suitability for academic performance. The findings of this paper show a significant result of TMG impact on student performance in Oman.